2021
DOI: 10.15408/ijee.v8i2.21135
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Learning Methods Employed by Language Teachers in the New Normal of COVID-19

Abstract: Learning activities should be conducted effectively to create conducive learning conditions to develop students’ creativity and their higher learning competence. Through conducting appropriate and effective learning activities, the learning objectives and learning competencies are easier to achieve. To create effective learning activities, teachers are required to have adequate understanding and competence in employing learning methods. This study aims to explore effective learning methods to create more creat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 9 publications
0
5
0
2
Order By: Relevance
“…As the pandemic spreads, its impact on education becomes concerning. When all the webinars are lulled by the discourse on handling education in health emergencies, the emergency situation for the quality of education actually happened much earlier maybe long before the COVID -19 outbreak (Mantra, Handayani, & Pramawati, 2021). With studying at home, children are also stressed and helpless for a long time so learning loss arises as a manifestation of the loss of children's opportunities to learn due to the demands of the applicable standards and curriculum.…”
Section: Learning Loss After the Covid-19 Pandemicmentioning
confidence: 99%
“…As the pandemic spreads, its impact on education becomes concerning. When all the webinars are lulled by the discourse on handling education in health emergencies, the emergency situation for the quality of education actually happened much earlier maybe long before the COVID -19 outbreak (Mantra, Handayani, & Pramawati, 2021). With studying at home, children are also stressed and helpless for a long time so learning loss arises as a manifestation of the loss of children's opportunities to learn due to the demands of the applicable standards and curriculum.…”
Section: Learning Loss After the Covid-19 Pandemicmentioning
confidence: 99%
“…The 21st century has brought significant changes to the education system, and teachers need to possess a wide range of skills to be effective in the modern classroom (Mantra et al, 2021). Teachers in the 21st-century education system must possess many skills to be effective in the contemporary classroom.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies found that the education system has undergone significant changes in the 21st century compared to past education (Widiastuti et al, 2022;Mantra et al, 2021;Maba, 2018). The 21st-century education system has become more student-centered, inclusive, collaborative, and technology-driven.…”
Section: Introductionmentioning
confidence: 99%
“…Assessment is also used to determine the strengths and weaknesses that exist in the learning process so that it can be used as a basis for decision-making (Kirby & Merchant, 2020). Therefore, in addition to a suitable curriculum and the right learning process, there needs to be a good and well-planned assessment system (Mantra et al, 2021).…”
Section: Introductionmentioning
confidence: 99%